TORCH SYNDROME - Valeriu Popescu (Amaltea Medical Publishing House, 2008)
The acronym "TORCH" represent a generic group of parasitic, bacterial and viral pathogens that produce congenital or perinatally acquired infections. TORCH stands for toxoplasmosis "other", rubella, cytomegalovirus (CMV) and herpes simplex. The "other" is an increasing number of agents responsible for fetal infections, such as varicella-zoster, parvovirus, human immunodeficiency virus (HIV), hepatitis B virus, Borrelia burgdorferi, syphilis.... Many of the clinical manifestations of TORCH infections are similar and include intrauterine growth retardation, nonimmune hydrops, anemia, thrombocytopenia, jaundice, hepatosplenomegaly, chorioretinitis and congenital malformations. Some of the unique manifestations and epidemiologic characteristics of these infections are noted in table 1